PENGEMBANGAN RECYCLE PARK BANK SAMPAH TERATAI MELALUI DIGITAL MARKETING LILIN AROMATERAPI - Rahayu, Sri; Indra; Ekawanti, Wahyumi (PORTAL RISET DAN INOVASI PENGABDIAN MASYARAKAT, 2023)
Recycle Park Bank Sampah is one of the social community organizations engaged in the environmental economy, especially in managing household waste for residents of RW 05 Pinang Griya Permai, Tangerang. Currently the Recycle Park Bank Sampah Teratai has 10 administrators as waste bank managers with a total number of customers of 59 people. Its existence is now very helpful to the Tangerang city government in reducing the accumulation of waste to the Final Disposal Site (TPA) in Rawa Kucing and helping to improve the economy of housewives, especially residents affected by the Covid-19 pandemic. Recycle Park Bank Sampah Teratai provides a place for residents of RW 05 Pinang Griya Permai to recycle using the 3R method (Reuse, Reduce, Recycle). The problems faced at the Recycle Park Bank Sampah Teratai are: 1) The Recycle Park Bank sampah Teratai activity program has not utilized used cooking oil waste optimally, 2) Lack of knowledge and skills of the Recycle Park Bank sampah Teratai management in packaging and marketing recycled waste products. These problems are due to partners having limited funds, facilities and human resources. This Community Service Program seeks to provide solutions to overcome these problems through: 1) Conducting training on making aromatherapy candles from used cooking oil for the community and management of the Recycle Park Bank Sampah Teratai, 2) Assisting in aromatherapy candle packaging and online marketing at market places.